Man and female impersonator - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a shirtless man with a female impersonator. The man has facial hair and wears a leather Greek fisherman's biker's cap with a silver chain. The female impersonator wears a light colored top and wig. A sign on the wall behind them reads: "Jan. 15-17 '88".